Evolution of Examination System of Bangladesh College of Physicians & Surgeons - Tarikul Islam, Quazi; Miah, Md Titu; Yasmin, Rubina; Das, Aparna; Rowshan, AHM; Alam, Md Billal; Rahman, Florida; Banik, Gobinda Chandra (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Bangladesh College of Physicians and Surgeons (BCPS) is the pioneer in pertaining postgraduate medical education and training in this country since its establishment on 6th June 1972. With tremendous effort from the founder Fellows, the BCPS was able to hold the first post-graduate examination in July 1972. In 1972, examination started with FCPS part I, II and MCPS Exam with four subjects. After 50 years journey of BCPS up to January 2022, number of fellows are 7479 and subjects of fellowship is 59.We have searched different papers and electronic documents of examination department of BCPS including year book and found that BCPS went through various changes occurred in different aspects of examination systems including number of subjects. Introduction of OSPE, SBA, IOE and omission of viva are the epoch-making steps of BCPS. Punctuality is the beauty of BCPS. But, at the era of golden jubilee of BCPS, our realization is that our examination system yet not structured and standardized up to the mark.We hope, BCPS will make a new horizon by overcoming all obstacles in future. J Bangladesh Coll Phys Surg 2022; 40: 39-45